South Africa : Financial Sector Assessment Program-Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT)-Technical Note. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses findings and recommendations made in the Financial Sector Assessment Program (FSAP) for South Africa in the areas of anti-money laundering and combating the financing of terrorism (AML/CFT). The AML/CFT supervisory framework for the financial sector, in particular the banking sector, has been strengthened by the amended Financial Intelligence Center (FIC) Act that took effect in 2010 and the creation of the AML/CFT supervision team within Banking Supervision Department (BSD) of the South African Reserve Bank (SARB). Significant technical deficiencies remain, such as the absence of requirements to identify and verify the identity of beneficial owners of customers and to apply enhanced diligence to high-risk situations.